The Burnout Inventory Level among Learning Disabilities Teachers Compared to General School Teachers in Makkah - Al-Sharif , Nahel Mohammed Babikir (Dirasat: Educational Sciences, 2020)
This study aims to detect the level of burnout inventory among learning disabilities teachers compared to general school teachers in Makkah. The study was conducted according to the causal-comparative design, using the Maslach & Jackson burnout inventory as a study tool. The sample of the study consisted of (275) female teachers, (25) were disabilities teachers, and (250) general school teachers were randomly selected from (231) schools from Makkah Al-Mukarramah schools for the academic year 1439-1440 AH. Results showed that Learning disabilities teachers and general school teachers had an Intermediate level of burnout inventory. Significant differences were found in teachers' level of burnout inventory in favor of the learning disabilities teachers, and there was a significant difference due to demographic variables. This Study recommends finding better criteria and mechanisms for selecting individuals who would apply for the teaching profession, to be able to deal positively with the pressures of the teaching profession and to avoid burnout inventory. In addition, holding training workshops for teachers aimed at providing them with the skills that will enable them to overcome the difficulties of working in the teaching profession.